(3ahVhjI GdYGde hejRGf Gdbhi (B:s (3gjcdI GdYGde GdLOjO hUQGY GdCQV hGdfaW hGdCShGb Gdi eG HYO SbhW HZOGO (B/s - (3YJQjSj, LYaQ MSfs ((3HjQhJ(B: s (3OGQ GdeMLI GdHjVGA ddWHGYI hGdfTQ(B, s, 2003)
(3GdahVhjI GdYGdejI aj GdbQf GdJGSY YTQ(B- (3GdahVhjI GdYGdejI aj GdbQf GdYTQjf(B- (3Gdechf GdJGQjNj ddbhi GdcHQi(B- (3GdYGde GdLOjO(B- (3YGde eG HYO GfgjGQ GdEJMGO GdShajGJj(B- (3ahVhjI GdYGde GdLOjO hEYGOI HfGA Gdbhi (B( (3GdUjf, QhSjG, GdhdGjGJ GdeJMOI GdCeQjcjI, GdTQb GdChSW(B)- (3GdEMJdGd GdCeQjcj ddYQGb(B- (3eG HYO SbhW HZOGO(B- (3efXeI GdeDJeQ GdESdGej hGdNWGH GdCeej(B.s
Keywords: (3GdCShGbs; (3GdSjGSI GdOhdjI GdfaWs; (3GdYdGbGJ GdEbJUGOjI GdOhdjIs; (3GdYdGbGJ GdNGQLjIs